Sexuality in Gbaya tales - (:unkn) unknown (My University, 2024)
The paper analyses the treatment of sexuality among the Gbaya of Central Africa. After presenting the Gbaya concept of the sexes, the author studies what is said about it, both in everyday expressions and in the various discursive genres identified in this culture: proverbs, riddles, legends, and finally tales. Tales explicitly address the sexual act and feature characters with exceptional, out-of-the-ordinary abilities, entirely in keeping with the imaginary world of storytelling, where excess is the rule. But these tales also offer an opportunity to stage elements of everyday life as commonly practised by everyone, where erotic games, foreplay and the enumeration of the usual stages in the progression of a sexual relationship illustrate the complementary roles of men and women, who are spoken of very freely. The tale is aimed at everyone, men, women and children, with no explicit didactic aim, but its repetition during storytelling evenings enables the acquisition and sharing of a common cultural knowledge while simultaneously succeeding as entertainment.
Keywords: African Research